2010
DOI: 10.1007/s00520-010-1005-8
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms during the first chemotherapy cycle predict mortality in patients with advanced non-small cell lung cancer

Abstract: The finding supports that depressive symptoms at the early phase of treatment can predict shorter survival in patients with advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
19
1
Order By: Relevance
“…Our HR of 2.21 before adjustment is similar to other studies , which examine depression on mortality. After adjusting for age, performance status and cancer stage, our HR of 4.13 was more than twice as high, but this was comparable with another local study which found that cancer patients with depressive symptomology were 4.31 times more likely (than those without) to experience mortality.…”
Section: Discussionsupporting
confidence: 88%
“…Our HR of 2.21 before adjustment is similar to other studies , which examine depression on mortality. After adjusting for age, performance status and cancer stage, our HR of 4.13 was more than twice as high, but this was comparable with another local study which found that cancer patients with depressive symptomology were 4.31 times more likely (than those without) to experience mortality.…”
Section: Discussionsupporting
confidence: 88%
“…26 Recent work demonstrated that interventions aimed at improving depressive severity and symptom control among those with NSCLC may also promote longer survival. 27 These interventions may be particularly beneficial for low SES individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lung cancer patients also have higher number of unmet psychological and daily living needs compared with patients with other malignancies . Despite the high prevalence, psychological distress remains largely unrecognized and suboptimally managed, which can lead to poorer quality of life, lower satisfaction with care, poorer adherence to treatment, and decreased survival …”
Section: Introductionmentioning
confidence: 99%